A New Electrochemical Method for the Estimation of Thermodynamic Parameters for Proton Transfer Between Strong Acids in Mixed Aqueous Solvents - Jumean, F.H. (Asian Journal of Chemistry, 2010)
Equations are derived for the thermodynamic parameters of proton transfer between two acids in mixed aqueous solvents of identical composition. These are applied to electrochemical data on HClO4 and HCl in tertiary butyl alcohol-water and DMF-water. HClO4 is shown to be completely ionised in both systems whereas HCl ionisation drops sharply with DMF addition but is unaffected by tertiary butyl alcohol. The partical molal free energy, enthalpy and entropy of transfer are obtained.